Prevalence and comorbidities associated with retinopathy in a specialized institution in Armenia Colombia (Revista de Investigaciones Universidad del Quindío, 2022)
Introduction: Hypertensive retinopathy and diabetic retinopathy constitute a public health problem because they generate avoidable visual impairment, however, the current prevalence, its associated factors in the region and its situation within the framework of the Comprehensive Health Care Routes are unknown (RIAS) for hypertension and diabetes that have established referral to ophthalmology as a follow-up of target organ damage.Objective: To describe the characteristics and comorbidities of Hypertensive and Diabetic retinopathy, in patients who consulted ophthalmology in Quindío during 2018.Methods: A descriptive cross-sectional study was carried out, based on the histories of patients who consulted a specialized institution in Quindío during 2018. Variables were described in mean, standard deviation and confidence intervals, a comparative analysis was made by sex, analysis of variance and Chi square were performed.Results: The prevalence of diabetic retinopathy was 1.65% and of hypertensive retinopathy 0.22%. 62.06% had non-proliferative diabetic retinopathy (NPDR) and 37.93% had proliferative diabetic retinopathy (PDR).Conclusions: More diabetic retinopathy is identified and hypertensive retinopathy is almost undiagnosed. And the number of patients who consult for eye diseases has been increasing during the last 3 years in a specialized center in the city of Armenia.
Keywords: Ophthalmology; Diabetic Retinopathy; Hypertensive Retinopathy